(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
A new canid species from the genus Eucyon-Eucyon marinae sp. nov. is described from the Late Ruscinian or the Early Villafranchian of Mongolia. The species is characterised by very specific large but narrow premolars and slender mandible. The paper also provide a discussion on the ecology of the species as well as a review of Late Miocene and Early Pliocene fossil canids from North America, Eurasia and Africa referable to the genus Euston. Problems related to the taxonomy of Eucyon and other Canis-like forms are discussed.